Strengthening the Governance of the Toba Caldera Geosite Through Adaptive Governance: Opportunities and Challenges - Hajar, Siti; Kholik, Kholilul; Kholis, Azizul (Indonesian Association for Public Administration (IAPA), 2025)
The adaptive governance approach is an important instrument in realizing sustainable tourism, thus the importance of managing Geopark areas that are not only oriented towards economic aspects, but also emphasize social, cultural, and environmental dimensions. The purpose of this study is to analyze the opportunities and challenges in strengthening the governance of the Toba Caldera Geosite in Samosir Regency. The method used is a qualitative case study. The results show that strengthening geosite governance has the opportunity to develop, because it is supported by UNESCO geopark regulations and has a GreenCard, local community involvement, although not optimal, and the potential for a creative economy based on Batak culture. However, the main challenges faced are limited inter-institutional coordination, low human resource capacity, and poor integration of cross-sectoral policies.